Halogen-free flame-retardant transparent nylon and preparation method thereof

By introducing phosphorus-based flame retardant and polysiloxane into transparent nylon and combining it with alcohol ether compounds, halogen-free flame retardant transparent nylon is prepared, which solves the problem of insufficient flame retardant performance of existing transparent nylon and achieves high The grade of flame retardant and mechanical properties are suitable for applications with high fire resistance requirements.

CN116355206BActive Publication Date: 2025-01-07WANHUA CHEM GRP CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202111610662.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-27
Publication Date
2025-01-07
Estimated Expiration
2041-12-27

AI Technical Summary

Technical Problem

The flame retardant performance of existing transparent nylon is insufficient, especially in the case of high fire hazards. The flame retardant grade can only reach HB and UL-94V2, which limits its application, and methods to improve flame retardancy will affect transparency and mechanical properties.

Method used

Composition of 4,4-diaminodicyclohexylmethane, long carbon chain aliphatic dibasic acid, bisamino-terminated organopolysiloxane, reactive phosphorus-based flame retardant, alcohol ether compound, catalyst and antioxidant Halogen-free flame-retardant transparent nylon is prepared by copolymerization method, combined with a lower content of phosphorus-based flame retardant to achieve the flame retardant grade of UL-94V0 while maintaining or improving mechanical properties.

Benefits of technology

It achieves flame retardant grade of UL-94V0 without losing transparent nylon mechanical properties, and significantly improves wear resistance. The oxygen index can reach 30-32%. It is suitable for automotive dials and electronic appliances with high fire resistance requirements. field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003434788880000031
    Figure BDA0003434788880000031
  • Figure BDA0003434788880000121
    Figure BDA0003434788880000121
  • Figure BDA0003434788880000122
    Figure BDA0003434788880000122
Patent Text Reader

Abstract

The present invention provides a halogen-free flame-retardant transparent nylon and a preparation method thereof. The raw materials used in the method include component A: a transparent nylon salt prepared from 4,4-diaminodicyclohexylmethane (PACM) or 3,3-dimethyl-4,4-diaminocyclohexylmethane (MACM) and a long carbon chain aliphatic dibasic acid; component B: a diamino-terminated organopolysiloxane; component C: a dicarboxyl-terminated reactive phosphorus flame retardant. The method of the present invention can prepare a transparent flame-retardant nylon with a flame retardant grade of UL-94V0 by introducing a special phosphorus-containing flame retardant and polysiloxane into the chain segment of transparent nylon. At the same time, the product has excellent transparency, wear resistance and impact resistance, and can be used in high-end application fields such as automobile liquid crystal display panels, automobile oil cups, and electronic and electrical housings, and has a wide range of application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of organic polymer materials, and specifically relates to a halogen-free flame-retardant transparent nylon and a preparation method thereof. Background Art

[0002] Transparent nylon is a thermoplastic nylon with an amorphous or microcrystalline structure. Its light transmittance can reach 90%. Its transparency is better than that of polycarbonate (PC) and close to that of polymethyl methacrylate (PMMA). Its environmental stress cracking resistance is better than that of PC and PMMA. At the same time, transparent nylon also has good thermal stability, impact toughness, electrical insulation, dimensional stability and aging resistance. The product has low shrinkage and linear expansion coefficient, and is resistant to dilute acids, alkalis, aliphatic hydrocarbons, aromatic hydrocarbons, esters, ethers, oils and fats. It can be used not only for beverage and food packaging, but also for packaging materials for automobile dashboards, electronic appliances, pharmaceutical chemicals, etc. The demand for transparent nylon in the market is also increasing.

[0003] Unmodified transparent nylon is copolymerized by alicyclic diamine 4,4-diaminodicyclohexylmethane (PACM) or 3,3-dimethyl-4,4-diaminocyclohexylmethane (MACM) with aliphatic long-chain dibasic acids. Its flame retardant properties are average, with an oxygen index of up to 26% and a flame retardant grade of only HB and UL-94V2. This, to a certain extent, limits the application of transparent nylon in situations with high fire hazards.

[0004] At present, the main methods for improving the flame retardancy of transparent nylon are random copolymerization and blending. Improving the flame retardancy of transparent nylon by blending will seriously affect the transparency of transparent nylon. Patent CN105504792A uses melamine and its derivatives and organic carboxylic acid compositions as flame retardants, and prepares transparent flame retardant nylon materials by melt blending and dispersion. This material has very excellent flame retardant properties, but the transparency of the product is not high, and it can only be regarded as a translucent nylon flame retardant material. Patent CN107189062A synthesizes phosphorus-containing flame retardants by reacting DOPO derivatives with diamines, and then copolymerizes the phosphorus-containing flame retardants with fatty acids and fatty amines to prepare flame-retardant transparent nylon. The flame-retardant transparent nylon prepared by this method has excellent flame retardancy and transparency, but the addition amount of phosphorus-based flame retardants is large, and the phosphorus element must reach a certain content in order for the material to have a good flame retardant effect. A higher content of phosphorus-based flame retardants will reduce the mechanical properties of transparent nylon, resulting in a reduction in the impact resistance, scratch resistance, and wear resistance of transparent nylon. Summary of the invention

[0005] The purpose of the present invention is to provide a halogen-free flame-retardant transparent nylon, which not only has excellent transparency and can meet the flame retardancy level of UL-94VO, but also takes into account the flame retardancy and transparency of transparent PA without losing the mechanical properties of transparent nylon itself, and the product has better wear resistance than ordinary transparent nylon.

[0006] In order to achieve the above invention object, the technical solution adopted by the present invention is as follows:

[0007] A halogen-free flame-retardant transparent nylon, which is polymerized from the following components:

[0008] Component A: Transparent nylon salt prepared from 4,4-diaminodicyclohexylmethane (PACM) or 3,3-dimethyl-4,4-diaminocyclohexylmethane (MACM) and long-chain aliphatic dibasic acid.

[0009] Component B: diamino-terminated organopolysiloxane,

[0010] Component C: dicarboxyl-terminated reactive phosphorus flame retardant,

[0011] The nylon further comprises an alcohol ether compound, a catalyst and an antioxidant.

[0012] In the present invention, the long carbon chain aliphatic dibasic acid in component A is one or more of sebacic acid, dodecanedioic acid, and tetradecanedioic acid, preferably dodecanedioic acid and / or tetradecanedioic acid. The longer the chain segment of the alkane, the better the softness of the product.

[0013] In the present invention, the structure of the diamino-terminated polysiloxane of component B is:

[0014]

[0015] Wherein, n is 5-30, preferably 10-20; preferably, the viscosity of the diamino-terminated polysiloxane at 25°C is 30-100 centipoise, preferably 50-80 centipoise at 25°C; preferably, the amount of the diamino-terminated polysiloxane accounts for 5-15‰, preferably 6-10‰ of the total mass of component A. The organic polysiloxane is copolymerized to the molecular main chain of flame-retardant transparent nylon by copolymerization, which can not only form a synergistic effect with the copolymerized P-series flame retardant to improve the flame retardant properties of the product, but also can reach the UL94-V0 flame retardant standard at a lower amount of P-series flame retardant, without losing the mechanical properties of transparent nylon, and can significantly improve the wear resistance of flame-retardant transparent nylon.

[0016] In the present invention, the C component reactive phosphorus flame retardant is a compound of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) containing a dicarboxyl group, bis(2-carboxyethyl)phosphonic acid, bis(2-carboxyethyl)methylphosphine oxide, 2-(2-methylphosphate)-4,6-(p-aminobenzoic acid)-s-triazine or more, preferably a compound of DOPO containing a dicarboxyl group and / or bis(2-carboxyethyl)phosphonic acid, more preferably a compound of DOPO containing a dicarboxyl group. The derivatives of DOPO containing dicarboxyl groups include 6-oxo-6H-dibenzo(c,e)(1,2)oxaphosphorin-6-one-succinic acid (DOPOMA), 6-oxo-6H-dibenzo(c,e)(1,2)oxaphosphorin-6-one-methyl-succinic acid (DDP), 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphorin-10-oxide (DOPO-HQ), etc. Preferably, the amount of reactive phosphorus flame retardant accounts for 1-3% of the total mass of component A, preferably 1.5-2%. The phosphorus flame retardant forms a dense carbon layer on the surface of the polymer to prevent further thermal decomposition of the material. At the same time, the water vapor generated by the dehydration of the surface of the combustion contact layer can dilute the concentration of oxygen, oxygen free radicals and combustible gases, and has a flame retardant effect through solid phase flame retardancy and gas phase flame retardancy.

[0017] In the present invention, the alcohol ether compound is a low-carbon compound of diethylene glycol and / or a low-carbon compound of dipropylene glycol, preferably one or more of diethanol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, diethylene glycol monopentyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, diethylene glycol monopropyl ether, and diethylene glycol monobutyl ether, more preferably diethylene glycol monobutyl ether and / or dipropylene glycol monobutyl ether, most preferably dipropylene glycol monobutyl ether. Alcohol ether compounds and reactive phosphorus-based flame retardants and dicarboxyl-terminated polysiloxanes can achieve a very good synergistic flame retardant effect. Preferably, the amount of the alcohol ether compound is 3-10‰ of the total mass of component A, preferably 4-8‰.

[0018] In the present invention, the antioxidant is selected from one or more of benzofuranone, hindered phenol, phosphite, thioester and thioether compound, and preferably the following three antioxidants are used in combination: 5,7-bis-(2,2-dimethylethyl)-3-(3,4-dimethylphenyl)-2-3 hydrogen-benzofuranone (antioxidant 136), N,N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine (antioxidant 1098), tris[2.4-di-tert-butylphenyl]phosphite (antioxidant 168); preferably, the amount of the three antioxidants used in combination is 1‰-5‰ of the total mass of component A.

[0019] In the present invention, the catalyst is one or more of sodium phosphate, sodium hypophosphite, and sodium hypophosphite, preferably sodium hypophosphite; preferably, the amount of the catalyst is 0.05‰-0.3‰ of the total mass of component A, preferably 0.05‰-0.2‰.

[0020] Optionally, the nylon of the present invention may also be added with a molecular weight regulator, wherein the molecular weight regulator is benzoic acid and / or glacial acetic acid, and the amount of the molecular weight regulator is determined according to the product formula and product viscosity.

[0021] Another object of the present invention is to provide a method for preparing halogen-free flame-retardant transparent nylon.

[0022] A method for preparing halogen-free flame-retardant transparent nylon, the method prepares the above-mentioned halogen-free flame-retardant transparent nylon, and the preparation process of the method is:

[0023] 4,4-diaminodicyclohexylmethane (PACM) or 3,3-dimethyl-4,4-diaminocyclohexylmethane (MACM), long-chain dibasic acid, reactive phosphorus flame retardant, diamine-terminated polysiloxane, alcohol ether compound, catalyst, antioxidant and water are added into the reactor, nitrogen replacement is performed, the temperature is increased and then the temperature is kept at the same temperature and pressure for reaction, stirring is started, heating is started so that the material is heated for the second time and then the temperature is kept at the same temperature and pressure for reaction, the pressure is released, the temperature is increased for the third time and then the vacuum reaction is continued, and the material is discharged and pelletized.

[0024] In the present invention, the heat-maintaining and pressure-maintaining reaction after heating is heating to 60-120° C. and then the heat-maintaining and pressure-maintaining reaction is carried out for 30-60 minutes.

[0025] In the present invention, the second heating and then continuing the heat preservation and pressure reaction is to slowly heat up to 200-220° C. and then keep the heat preservation and pressure for 60-120 minutes.

[0026] In the present invention, the three times of heating and continuing vacuuming reaction are heating to 240-260° C. and then vacuuming for 30-60 minutes.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The present invention prepares halogen-free flame-retardant transparent nylon by introducing phosphorus-based flame retardant and polysiloxane into the main chain of transparent nylon and compounding a trace amount of alcohol ether compound. Under the condition of adding a relatively low content of phosphorus-based flame retardant, the flame retardant grade of the prepared transparent nylon can reach UL-94V0, and the limiting oxygen index can reach 30-32%. Compared with ordinary transparent nylon, the mechanical strength of the prepared flame-retardant transparent nylon is not reduced, and its wear resistance is further improved. It can be used in the fields of automobile dials, electronic and electrical appliance shells, etc. that have relatively high requirements for fire protection level, and has broad application prospects. DETAILED DESCRIPTION

[0029] The following examples further illustrate preferred specific embodiments within the scope of the present invention. These examples are merely illustrative and are not intended to limit the scope of the present invention, as many variations of the present invention may be made without departing from the spirit and scope thereof.

[0030] Processing and standard equipment information:

[0031] Twin-screw extruder: Nanjing Jieya twin-screw extruder SH-42;

[0032] Injection molding machine: Haitian injection molding machine ZE1200;

[0033] Density tester: Lichen Technology XF-200S;

[0034] Universal tensile testing machine: Shimadzu AGX-V electronic universal testing machine;

[0035] Impact strength tester: Instron CEAST 9050;

[0036] Colorimeter: Hunterlab Vista spectrophotometer;

[0037] Abrasion tester: Taber abrasion tester 1700;

[0038] Limiting oxygen index instrument: GT-LOIA;

[0039] Horizontal vertical combustion instrument: High-speed rail GT-7057-94 horizontal vertical combustion test instrument.

[0040] The raw material information is as follows:

[0041] 4,4-Diaminodicyclohexylmethane (PACM50) is PACM from Shenzhen Yexu Biotechnology Co., Ltd., purity> 99% (chromatographic method)

[0042] 3,3-Dimethyl-4,4-diaminocyclohexylmethane (MACM) is from Shenzhen Yexu Biotechnology Co., Ltd., with a purity of >99% (chromatographic method)

[0043] Dodecanedioic acid is from Ube Industries, Japan, purity>99% (chromatographic method)

[0044] Tetradecanedioic acid is DC14 from Shanghai Kaisai Biotechnology Co., Ltd., purity> 98.5% (chromatographic method)

[0045] Sebacic acid is DC10 from Shanghai Kaisai Biotechnology Co., Ltd., purity>99.5 (chromatographic method)

[0046] DDP is the flame retardant DDP of Shouguang Puer Chemical Co., Ltd., purity> 99% (chromatographic method)

[0047] Diethylene glycol monobutyl ether is diethylene glycol monobutyl ether from Dow Chemical, purity>99% (chromatographic method)

[0048] Dipropylene glycol monobutyl ether is dipropylene glycol monobutyl ether from Dow Chemical, purity>99% (chromatographic method)

[0049] The bisamino-terminated polysiloxane is DY-N201 produced by Shandong Dayi Chemical Co., Ltd. and includes three varieties with room temperature viscosities of 30, 50, and 100 centipoise.

[0050] Comparative Example 1

[0051] Comparative Example 1 is a conventional PACM system transparent nylon formulation. Compared with Example 1, DDP, diamino-terminated polysiloxane and alcohol ether compound are not added to the comparative example.

[0052] 959.11 g 4,4-diaminodicyclohexylmethane (PACM50), 1000 g dodecanedioic acid, 600 g water, 0.37 g phosphoric acid, 62.34 g adipic acid, 2 g antioxidant 136, 2 g antioxidant 1098 and 2 g antioxidant 168 were added to the reactor. After nitrogen replacement for 3 times, the temperature was raised to 110°C, and the temperature and pressure were kept for 40 minutes to carry out salt-forming reaction. Then, stirring was started, the reaction temperature was raised to 220°C, and the temperature and pressure were kept for 2 hours to carry out prepolymerization reaction. Then, the pressure was released to normal pressure, and the temperature was raised to 270°C at the same time. The mixture was evacuated to -90 kPaG, and the reaction was continued for 30 minutes before discharging and pelletizing.

[0053] Comparative Example 2

[0054] Comparative Example 2 is a formula of transparent nylon of a conventional MACM system. Compared with Example 2, DDP, diamino-terminated polysiloxane and alcohol ether compound are not added in the comparative example.

[0055] 1086.56g of 3,3-dimethyl-4,4-diaminocyclohexylmethane (MACM), 1000g of dodecanedioic acid, 600g of water, 0.31g of sodium hypophosphite, 62.34g of adipic acid, 2g of antioxidant 136, 2g of antioxidant 1098 and 2g of antioxidant 168 were added to the reactor. After nitrogen replacement for 3 times, the temperature was raised to 110°C, and the temperature and pressure were kept for 40min to carry out salt-forming reaction. Then, stirring was started, the reaction temperature was raised to 220°C, and the temperature and pressure were kept for 2h to carry out prepolymerization reaction. Then, the pressure was released to normal pressure, and the temperature was raised to 270°C at the same time. The mixture was evacuated to -90kPaG, and the reaction was continued for 30min before discharging and pelletizing.

[0056] Comparative Example 3

[0057] Comparison of Comparative Example 3 with Example 1 shows that only DDP is added in the Comparative Example, and no diamino-terminated polysiloxane and alcohol ether compound are added.

[0058] 1003.37 g of 4,4-diaminodicyclohexylmethane (PACM50), 1000 g of dodecanedioic acid, 40.37 g of DDP, 600 g of water, 0.31 g of sodium hypophosphite, 62.34 g of adipic acid, 2 g of antioxidant 136, 2 g of antioxidant 1098 and 2 g of antioxidant 168 were added to the reactor. After nitrogen replacement for 3 times, the temperature was raised to 110°C, and the reaction was kept at temperature and pressure for 40 minutes to carry out a salt-forming reaction. Then, stirring was started, the reaction temperature was raised to 220°C, and the reaction was kept at temperature and pressure for 2 hours to carry out a prepolymerization reaction. Then, the pressure was released to normal pressure, and the temperature was raised to 270°C at the same time. The mixture was evacuated to -90 kPaG, and the reaction was continued for 30 minutes before discharging and pelletizing.

[0059] Comparative Example 4

[0060] Comparison Example 4 with Example 2 shows that only DDP is added in the comparative example, and no diamino-terminated polysiloxane and alcohol ether compound are added.

[0061] 1087.56g of 3,3-dimethyl-4,4-diaminocyclohexylmethane (MACM), 1000g of dodecanedioic acid, 40.37g of DDP, 600g of water, 0.31g of sodium hypophosphite, 62.34g of adipic acid, 2g of antioxidant 136, 2g of antioxidant 1098 and 2g of antioxidant 168 were added to the reactor. After nitrogen replacement for 3 times, the temperature was raised to 110°C, and the reaction was kept at temperature and pressure for 40min to carry out salt-forming reaction. Then, stirring was started, the reaction temperature was raised to 220°C, and the reaction was kept at temperature and pressure for 2h to carry out prepolymerization reaction. Then, the pressure was released to normal pressure, and the temperature was raised to 270°C at the same time. The mixture was evacuated to -90kPaG, and the reaction was continued for 30min before discharging and pelletizing.

[0062] Comparative Example 5

[0063] Comparative Example 5 Compared with Example 2, a higher content of DDP and diamino-terminated polysiloxane was added in the comparative example, and no alcohol ether compound was added.

[0064] 1048.37g of 4,4-diaminodicyclohexylmethane (PACM50), 1000g of dodecanedioic acid, 100.26g of DDP, 31.2g of diamino-terminated polysiloxane, 600g of water, 0.31g of sodium hypophosphite, 62.34g of adipic acid, 2g of antioxidant 136, 2g of antioxidant 1098, and 2g of antioxidant 168 were added to the reactor. After nitrogen replacement 3 times, the temperature was raised to 110°C, and the temperature and pressure were kept for 40min to carry out salt-forming reaction. Then, stirring was started, the reaction temperature was raised to 220°C, and the temperature and pressure were kept for 2h to carry out prepolymerization reaction. Then, the pressure was released to normal pressure, and the temperature was raised to 270°C at the same time. The mixture was evacuated to -90kPaG, and the reaction was continued for 30min before discharging and pelletizing.

[0065] Example 1

[0066] 1003.37 g of 4,4-diaminodicyclohexylmethane (PACM50), 1000 g of dodecanedioic acid, 42.37 g of DDP, 16.25 g of 50 centipoise terminal amine-terminated polysiloxane, 12.25 g of dipropylene glycol monobutyl ether, 600 g of water, 0.31 g of sodium hypophosphite, 62.34 g of adipic acid, 2 g of antioxidant 136, 2 g of antioxidant 1098, and 2 g of antioxidant 168 were added to the reactor. After nitrogen replacement three times, the temperature was raised to 110° C., and the reaction was kept at temperature and pressure for 40 minutes before salt formation reaction. Then, stirring was started, the reaction temperature was raised to 220° C., and the reaction was kept at temperature and pressure for 2 hours for prepolymerization reaction. Then the pressure was released to normal pressure, and the temperature was raised to 270° C. at the same time, and the mixture was evacuated to -90 kPaG. After the reaction was continued for 30 minutes, the material was discharged and pelletized.

[0067] Example 2

[0068] 1087.56g of 3,3-dimethyl-4,4-diaminocyclohexylmethane (MACM), 1000g of dodecanedioic acid, 41.65g of DDP, 20.87g of 50 centipoise viscosity diamino-terminated polysiloxane, 600g of water, 0.31g of sodium hypophosphite, 62.34g of adipic acid, 16.12g of diethylene glycol monobutyl ether, 2g of antioxidant 136, 2g of antioxidant 1098, and 2g of antioxidant 168 were added to the reactor. After nitrogen replacement 3 times, the temperature was raised to 110°C, and the temperature was kept at 110°C for 40min to carry out salt-forming reaction. Then, stirring was started, the temperature was raised to 220°C, and the temperature was kept at 110°C for 2h to carry out prepolymerization reaction. Then, the pressure was released to normal pressure, and the temperature was raised to 270°C at the same time. The mixture was evacuated to -90kPaG, and the reaction was continued for 30min before discharging and pelletizing.

[0069] Example 3

[0070] 1087.56g of 3,3-dimethyl-4,4-diaminocyclohexylmethane (MACM), 1000g of tetradecanedioic acid, 61.86g of DDP, 10.21g of 50 centipoise viscosity diamino-terminated polysiloxane, 600g of water, 0.31g of sodium hypophosphite, 62.34g of adipic acid, 8.36g of dipropylene glycol monobutyl ether, 2g of antioxidant 136, 2g of antioxidant 1098, and 2g of antioxidant 168 were added to the reactor. After nitrogen replacement three times, the temperature was raised to 110°C, and the temperature was kept at room temperature and pressure for 40min to carry out salt-forming reaction. Then, stirring was started, the reaction temperature was raised to 220°C, and the temperature was kept at room temperature and pressure for 2h to carry out prepolymerization reaction. Then, the pressure was released to normal pressure, and the temperature was raised to 270°C at the same time. The mixture was evacuated to -90kPaG, and the reaction was continued for 30min before discharging and pelletizing.

[0071] Example 4

[0072] 1003.37g of 3,3-dimethyl-4,4-diaminocyclohexylmethane (MACM), 1000g of sebacic acid, 22.37g of DDP, 30.25g of 30 centipoise viscosity terminal amino-terminated polysiloxane, 600g of water, 0.31g of sodium hypophosphite, 62.34g of adipic acid, 20.27g of dipropylene glycol monobutyl ether, 2g of antioxidant 136, 2g of antioxidant 1098, and 2g of antioxidant 168 were added to the reactor. After nitrogen replacement three times, the temperature was raised to 110°C, and the temperature was kept at room temperature and pressure for 40min to carry out salt-forming reaction. Then, stirring was started, the reaction temperature was raised to 220°C, and the temperature was kept at room temperature and pressure for 2h to carry out prepolymerization reaction. Then, the pressure was released to normal pressure, and the temperature was raised to 270°C at the same time. The mixture was evacuated to -90kPaG, and the reaction was continued for 30min before discharging and pelletizing.

[0073] Example 5

[0074] 1003.37 g of 4,4-diaminodicyclohexylmethane (PACM50), 1000 g of tetradecanedioic acid, 30.19 g of DDP, 12.25 g of 100 centipoise viscosity terminal amino-terminated polysiloxane, 600 g of water, 0.31 g of sodium hypophosphite, 62.34 g of adipic acid, 6.17 g of dipropylene glycol monobutyl ether, 2 g of antioxidant 136, 2 g of antioxidant 1098, and 2 g of antioxidant 168 were added to the reactor. After nitrogen replacement three times, the temperature was raised to 110° C., and the temperature was kept at 110° C. for 40 min to carry out salt-forming reaction. Then, stirring was started, the temperature was raised to 220° C., and the temperature was kept at 110° C. for 2 h to carry out prepolymerization reaction. Then, the pressure was released to normal pressure, and the temperature was raised to 270° C. at the same time, and the temperature was evacuated to -90 kPaG. After the reaction was continued for 30 min, the material was discharged and pelletized.

[0075] Example 6

[0076] 1087.56g of 4,4-diaminodicyclohexylmethane (PACM50), 1000g of sebacic acid, 30.17g of DDP, 20.28g of 50 centipoise viscosity diamino-terminated polysiloxane, 600g of water, 0.31g of sodium hypophosphite, 62.34g of adipic acid, 16g of dipropylene glycol monobutyl ether, 2g of antioxidant 136, 2g of antioxidant 1098, and 2g of antioxidant 168 were added to the reactor. After nitrogen replacement three times, the temperature was raised to 110°C, and the temperature was kept at room temperature and pressure for 40min to carry out salt-forming reaction. Then, stirring was started, the reaction temperature was raised to 220°C, and the temperature was kept at room temperature and pressure for 2h to carry out prepolymerization reaction. Then, the pressure was released to normal pressure, and the temperature was raised to 270°C at the same time, and the temperature was evacuated to -90kPaG. After continuing the reaction for 30min, the material was discharged and pelletized.

[0077] Example 7

[0078] 1003.37 g of 4,4-diaminodicyclohexylmethane (PACM50), 1000 g of dodecanedioic acid, 41.37 g of DDP, 16.25 g of 50 centipoise terminal amine-terminated polysiloxane, 600 g of water, 0.31 g of sodium hypophosphite, 62.34 g of adipic acid, 12.01 g of diethylene glycol monobutyl ether, 2 g of antioxidant 136, 2 g of antioxidant 1098, and 2 g of antioxidant 168 were added to the reactor. After nitrogen replacement three times, the temperature was raised to 110° C., and the temperature was kept at 110° C. for 40 min to carry out salt-forming reaction. Then, stirring was started, the temperature was raised to 220° C., and the temperature was kept at 110° C. for 2 h to carry out prepolymerization reaction. Then, the pressure was released to normal pressure, and the temperature was raised to 270° C. at the same time, and the temperature was evacuated to -90 kPaG. After the reaction was continued for 30 min, the material was discharged and pelletized.

[0079] Example 8

[0080] 1087.56 g of 4,4-diaminodicyclohexylmethane (PACM50), 1000 g of tetradecanedioic acid, 40.76 g of DDP, 18.28 g of 50 centipoise viscosity diamino-terminated polysiloxane, 600 g of water, 0.31 g of sodium hypophosphite, 62.34 g of adipic acid, 20.35 g of diethylene glycol monobutyl ether, 2 g of antioxidant 136, 2 g of antioxidant 1098, and 2 g of antioxidant 168 were added to the reactor. After nitrogen replacement three times, the temperature was raised to 110° C., and the temperature was kept at 110° C. for 40 min to carry out salt-forming reaction. Then, stirring was started, the temperature was raised to 220° C., and the temperature was kept at 110° C. for 2 h to carry out prepolymerization reaction. Then, the pressure was released to normal pressure, and the temperature was raised to 270° C. at the same time, and the temperature was evacuated to -90 kPaG. After the reaction was continued for 30 min, the material was discharged and pelletized.

[0081] The data test results of the comparative examples and embodiments are as follows:

[0082]

[0083]

[0084]

[0085] By comparing the comparative examples with the examples, it can be found that by compounding the alcohol ether compound, the phosphorus-containing flame retardant, and the diamino-terminated polysiloxane, under the condition of adding a small amount of reactive phosphorus-based flame retardant, the flame retardant grade of the product can reach UL 94-V0, the oxygen index is between 30-32, and the product has very excellent wear resistance and impact resistance, and the transparency of the product is above 91%. It is very suitable for automotive instrument panels, electronic appliances and other fields with high flame retardancy requirements.

[0086] The above embodiments are only for illustrating the technical concept and features of the present invention, and cannot be used to limit the protection scope of the present invention. Any changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A halogen-free flame-retardant transparent nylon, characterized in that: The nylon is polymerized from the following components: Component A: Transparent nylon salt prepared from 4,4-diaminodicyclohexylmethane (PACM) or 3,3-dimethyl-4,4-diaminocyclohexylmethane (MACM) and long-chain aliphatic dibasic acid. Component B: diamino-terminated organopolysiloxane, Component C: dicarboxyl-terminated reactive phosphorus flame retardant, The nylon further comprises an alcohol ether compound, a catalyst, and an antioxidant; Wherein, the structure of the diamino-terminated polysiloxane of component B is: Wherein, n is 5-30; Wherein, the amount of the diamino-terminated polysiloxane is 5-15‰ of the total mass of component A; The amount of the reactive phosphorus-based flame retardant is 1-3% of the total mass of component A; The amount of the alcohol ether compound used is 3-10‰ of the total mass of component A.

2. The nylon according to claim 1, characterized in that The long carbon chain aliphatic dibasic acid in the A component is one or more of sebacic acid, dodecanedioic acid, and tetradecanedioic acid.

3. The nylon according to claim 2, characterized in that: The long carbon chain aliphatic dibasic acid in the component A is dodecanedioic acid and / or tetradecanedioic acid.

4. The nylon according to claim 1, characterized in that In the diamino-terminated polysiloxane structure of component B, n is 10-20; The amount of the diamino-terminated polysiloxane used accounts for 6-10‰ of the total mass of component A.

5. The nylon according to claim 4, characterized in that The viscosity of the bisamino-terminated polysiloxane is 30-100 centipoise at 25°C.

6. The nylon according to claim 5, characterized in that The viscosity of the bisamino-terminated polysiloxane is 50-80 centipoise at 25°C.

7. The nylon according to claim 1, characterized in that The C component reactive phosphorus flame retardant is one or more of a dicarboxyl-containing 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) compound, bis(2-carboxyethyl)phosphonic acid, bis(2-carboxyethyl)methylphosphine oxide, and 2-(2-methylphosphate)-4,6-(p-aminobenzoic acid)-s-triazine.

8. The nylon according to claim 7, characterized in that The C-component reactive phosphorus-based flame retardant is a DOPO compound containing a dicarboxyl group and / or bis(2-carboxyethyl)phosphonic acid.

9. The nylon according to claim 8, characterized in that The C component reactive phosphorus-based flame retardant is a DOPO compound containing a dicarboxyl group; The amount of the reactive phosphorus-based flame retardant used accounts for 1.5-2% of the total mass of component A.

10. The nylon according to claim 1, characterized in that The alcohol ether compound is a low-carbon compound of diethylene glycol and / or a low-carbon compound of dipropylene glycol.

11. The nylon according to claim 10, characterized in that The alcohol ether compound is one or more of diethanol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monopropyl ether, diethylene glycol monobutyl ether, diethylene glycol monopentyl ether, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, diethylene glycol monopropyl ether and diethylene glycol monobutyl ether.

12. The nylon according to claim 11, characterized in that The alcohol ether compound is diethylene glycol monobutyl ether and / or dipropylene glycol monobutyl ether; The amount of the alcohol ether compound used is 4-8‰ of the total mass of component A.

13. The nylon according to claim 12, characterized in that The alcohol ether compound is dipropylene glycol monobutyl ether.

14. The nylon according to claim 1, characterized in that The antioxidant is selected from one or more of benzofuranone, hindered phenol, phosphite, thioester and thioether complex.

15. The nylon according to claim 14, characterized in that The antioxidant is used in combination with the following three antioxidants: 5,7-bis-(2,2-dimethylethyl)-3-(3,4-dimethylphenyl)-2-3 hydrogen-benzofuranone (antioxidant 136), N,N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine (antioxidant 1098), tris[2,4-di-tert-butylphenyl]phosphite (antioxidant 168); The dosage of the three antioxidants used in combination is 1‰-5‰ of the total mass of component A respectively.

16. The nylon according to claim 1, characterized in that The catalyst is one or more of sodium phosphate, sodium hypophosphite and sodium hypophosphite.

17. The nylon according to claim 16, characterized in that The catalyst is sodium hypophosphite; The amount of catalyst used is 0.05‰-0.3‰ of the total mass of component A.

18. The nylon according to claim 17, characterized in that The amount of catalyst used is 0.05‰-0.2‰ of the total mass of component A.

19. A method for preparing halogen-free flame-retardant transparent nylon, wherein the method prepares the halogen-free flame-retardant transparent nylon according to any one of claims 1 to 18, characterized in that: The preparation process of the method is: 4,4-diaminodicyclohexylmethane (PACM) or 3,3-dimethyl-4,4-diaminocyclohexylmethane (MACM), long-chain dibasic acid, reactive phosphorus flame retardant, diamine-terminated polysiloxane, alcohol ether compound, catalyst, antioxidant and water are added into the reactor, nitrogen replacement is performed, the temperature is increased and then the temperature is kept at the same temperature and pressure for reaction, stirring is started, heating is started so that the material is heated for the second time and then the temperature is kept at the same temperature and pressure for reaction, the pressure is released, the temperature is increased for the third time and then the vacuum reaction is continued, and the material is discharged and pelletized.

20. The preparation method according to claim 19, characterized in that: The heat preservation and pressure keeping reaction after heating is heating to 60-120° C. and then the heat preservation and pressure keeping reaction is carried out for 30-60 minutes; And / or, the heat preservation and pressure keeping reaction after the second heating is to slowly heat up to 200-220° C. and then keep the temperature and pressure keeping reaction for 60-120 min; And / or, the three times of heating and continuing vacuuming reaction are heating to 240-260° C. and then vacuuming for 30-60 minutes.

Citation Information

Patent Citations

  • Transparent flame-retardant nylon resin and preparation method thereof

    CN105504792A

  • Low-melting-point and flame-retarding copolymerized nylon and preparation method thereof

    CN107189062A

  • Transparent, amorphous polyamide molding compositions and their use

    CN101050303A

  • Silicon-containing reactive flame retardant nylon resin and preparation method thereof

    CN106700067A